Learning Commons: Konsep Pengembangan Perpustakaan Perguruan Tinggi Menghadapi Generasi Digital - Muhammad Choironi Yusuf (IAIN Ponorogo, 2015)
n the digital age, when information can be accessed without any limits of space and time, has given the considerable impact of the library. During this period, the existence of library started to be questioned. Information search behavior changes and the changing needs of the library makes a librarian sued to be able to keep abreast of the latest developments in managing a library. To answer this need, the idea of learning commons appears, by changing the concept of management of libraries that are adapted to the character of the digital generation. The concept of learning commons present in an efort to ofset any change in behavior of the digital generation in utilizing community library. Creating Library learning commons-based does not mean having to pay, but the most important is how to change the mindset of librarian.